Time course determination of the effects of rapid and gradual cooling after acute hyperthermia on body temperature and intestinal integrity in pigs. (January 2020) - Kpodo, Kouassi R.; Duttlinger, Alan W.; Radcliffe, John S.; Johnson, Jay S.
Abstract: Rapid cooling after acute hyperthermia may cause a sustained increase in body temperature and exacerbate intestinal damage in pigs. Therefore, the study objective was to evaluate the temporal effects of rapid and gradual cooling on body temperature response and intestinal integrity after acute hyperthermia in pigs. In three repetitions, 54 pigs [83.3 ± 6.7 kg initial body weight (BW )], balanced by sex were exposed to thermoneutral conditions for 6 h (TN ; n = 6 pigs/repetition; 21.1 ± 2.0°C), or heat stress conditions (HS ; 39.3 ± 1.6°C) for 3 h, followed by a 3 h recovery period of gradual cooling [HSGC ; n = 6 pigs/repetition; gradual decrease from HS to TN conditions] or rapid cooling [HSRC ; n = 6 pigs/repetition; rapid TN exposure and cold water (4.0°C) dousing every 30 min for 1.5 h]. Feed was withheld throughout the entire 6 h period, but water was provided ad libitum . Gastrointestinal (T GI ) and rectal (T R ) temperatures were recorded every 15 min during the HS and recovery periods. Six pigs per repetition (n = 2/treatment) were euthanized and jejunal and ileal samples were collected for histology immediately after (d 0), 2 d after, and 4 d after the recovery period. Data were analyzed using PROC MIXED in SAS 9.4. Overall, rapid cooling reduced TR and TGI ( P  < 0.01; 0.95°C and 0.74°C, respectively) compared to gradual cooling. Jejunal villus height was reduced overall ( P  = 0.02; 14.01%) in HSGC compared to HSRC and TN pigs. Jejunal villus height-to-crypt depth ratio was reduced overall ( P  = 0.05; 16.76%) in HSGC compared to TN pigs. Ileal villus height was reduced overall ( P  < 0.01; 16.95%) in HSGC compared to HSRC and TN pigs. No other intestinal morphology differences were detected. In summary, HSRC did not cause a sustained increase in body temperature and did not negatively impact biomarkers of intestinal integrity in pigs. Highlights: Rapid cooling without feed access reduced gastrointestinal temperature compared to gradual cooling. Rapid cooling without feed access reduced rectal temperature below thermoneutral pig levels. Rapid cooling without feed access prevented intestinal damage resulting from acute hyperthermia.